Challenges to Implement Technology Assisted English Language Teaching in Nepal: An Explorative Study - Lamichhane, Sujana (Studies in ELT and Applied Linguistics, 2025)
This paper investigates the various dimensions of the challenges to the technology assisted English language teaching faced by the secondary level English teachers of public schools from Kathmandu. The emergence and use of ICT and other innovative technologies in the teaching learning process demands restructuring in the English classrooms. Even though there exist a number of challenges and obstacles to adopt technology assisted teaching of English language skills, the study is focused towards prioritizing those challenges and suggesting some possible solutions to tackle them. The study is based on the qualitative research design and includes the in-depth interview with five purposively selected English teachers from the different schools. The study also includes the classroom observation for data collection. The data obtained were recorded and analyzed thematically based on the participant’s perception and experiences. The findings indicate that the poor economic status, insufficient physical resources, lack of digital competency among teachers to adopt technology and the conventional curriculum design remain as the major challenges. The article recommends some policy intervention for improving the socio-economic condition of the families sending their children to the public schools so that they can afford to access the necessary devices, ICT tools and platforms. Allocation of sufficient budget as an investment in the technology friendly classrooms, periodic training to the teachers for enhancing teaching skills and timely amendment in the curriculum are the few suggestive measures to combat the challenges.